Mapeamento cruzado entre termos da linguagem especial de enfermagem para a prática junto a povos indígenas e os termos da classificação internacional para a prática de enfermagem CIPE® - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
INTRODUCTION: In this context of indigenous health, the nurse's work is full of challenges that permeate geographic, epidemiological and cultural issues. This requires from these professionals, care models that are sensitive to the population's way of life, supported by a standardized language system and evidence-based protocols, generating documentation of records of nursing professionals' practices, thus, the absence of a common language for nursing professionals. nursing professionals working with these people is one of the biggest challenges when it comes to recording the care offered. OBJECTIVE: To develop a cross-mapping guide between nursing language terms for practice with indigenous peoples in the Amazonian context with the terms of the seven-axis model of the International Classification for Nursing Practice - ICNP®, version 2019/2020. METHOD: This is an exploratory, descriptive study with a qualitative approach. The methodological process used was based on cross-mapping, translated as mapeamento cruzado, which makes it possible to map and compare nursing records made with non-standardized terminologies in reference classifications with standardized language. Mapping is the second stage of the Brazilian method for developing ICNP® terminological subsets. The basis for the mapping is published in the “Glossary of Special Nursing Language for Practice with Indigenous Peoples in the Amazon Context”, which presents 764 terms. For mapping, this set of terms is called “source document”. In turn, the terms CIPE® 2019/2020 is called “target document”. The automated mapping was carried out using a computational tool called MappICNP, which contains rules from natural language processing (NLP), and was originally developed for mapping between a set of natural language terms and the terms of the Systematized Nomenclature of Medicine Clinical Terms (SNOMED-CT). Terms not mapped by MappICNP were manually analyzed by the team's researchers, using the equivalence scale of the ISO/TR 12300:2016 standard. RESULTS: Processing using the MappICNP tool generated the following results: 356 (46.6%) terms with direct mapping (exact encounter between terms); 15 (2.0%) terms reduced to their radical; 110 (14.4%) more comprehensive terms; 33 (4.3%) more restricted terms, and 232 (30.4%) terms were not mapped with ICNP®. Manual mapping of these terms resulted in: 39 (16.8%) with lexical and conceptual equivalence; 19 (8.2%) with equivalence of meaning, with synonymy; 50 (21.5%) were considered broader and with less specific meaning than the target term; 103 (44.4%) were considered more restricted and with more meaning than the target term; and 21 (9.1%) no mapping was possible. 18 (2.3%) terms were excluded because they were abbreviated terms previously described without abbreviations. FINAL CONSIDERATIONS: The cross-mapping between these terms seeks to establish a bridge between the technical language of nursing and practical application in intercultural contexts, ensuring that nursing care is provided, supported by the Nursing Process through standardized terminologies, in particular, based on the Seven Axis model of the International Classification for Nursing Practice (ICNP®), respecting the traditional knowledge and practices of indigenous peoples.
Keywords: CIENCIAS DA SAUDE: SAUDE COLETIVA: SAUDE PUBLICA; Saúde de populações indígenas; Terminologia padronizada em enfermagem; Classificação; Mapeamento cruzado